Revitalizing material interpretations: augmenting learning in online architectural education through material embodiment and communication - Cimşit Koş, Fitnat; Aşkın Kütükçü, Seben; Cinar Balci, Ece (Estoa. Journal of the Faculty of Architecture and Urbanism, 2025)
Material augmentation and communication techniques in online education enhance architectural thinking and creation, opening new avenues for design exploration. By focusing on responsive constructions and unconventional modeling techniques, this study fosters a more immersive and expressive design approach. The methodology unfolds in three phases: local mapping based on environmental experiences, exploration of alternative material deviations, and the development of new tectonic principles through material representation. These phases critically examine the interaction between modeling techniques and material variations, aligning reality with representative preferences. The primary aim is to challenge conventional architectural modeling through dynamic processes and material perception strategies. Ultimately, the study offers alternative processes centered on materials and communication tools, enriching the educational experience by promoting deeper sensory and intellectual connections with the built environment for future architects.